Leaving Emergency Management in the Refugee Crisis to Civil Society? The Case of Austria. Issue 1 (2nd January 2017) - Simsa, Ruth
ABSTRACT: This article assesses the role of Austrian civil society in the refugee crisis. Based on empirical research conducted in the autumn and winter of 2015, the activities of civil society actors, the framework conditions and their consequences will be shown. The influx of hundreds of thousands asylum seekers in 2015 was and is a crucial challenge for social integration, security, and stability in many European countries. In the period concerned, Austria was one of the countries confronted to an extremely high degree with both asylum seekers and transit refugees. Civil society actors such as nonprofit organizations (NPOs) and volunteers played an important role in maintaining humanitarian standards and effective crisis management, yet at a high cost and strain especially for civil society actors, NPOs, and volunteers.